2012
DOI: 10.1208/s12248-012-9373-2
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Methods for Handling Missing Categorical Covariate Data in Population Pharmacokinetic Analyses

Abstract: In population pharmacokinetic analyses, missing categorical data are often encountered. We evaluated several methods of performing covariate analyses with partially missing categorical covariate data. Missing data methods consisted of discarding data (DROP), additional effect parameter for the group with missing data (EXTRA), and mixture methods in which the mixing probability was fixed to the observed fraction of categories (MIX(obs)), based on the likelihood of the concentration data (MIX(conc)), or combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 18 publications
(16 reference statements)
0
38
0
Order By: Relevance
“…Genotype information regarding CES1 diplotypes, rs71647871, and rs115629050 was missing in 0.8%, 5%, and 42%, respectively, of the total studied population. Missing data were considered as being missing not at random and was handled using the EXTRA (or EST) method . Gender was included on MTT due to the improvement of model fit assessed through decrease of OFV and improvement of visual diagnostics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotype information regarding CES1 diplotypes, rs71647871, and rs115629050 was missing in 0.8%, 5%, and 42%, respectively, of the total studied population. Missing data were considered as being missing not at random and was handled using the EXTRA (or EST) method . Gender was included on MTT due to the improvement of model fit assessed through decrease of OFV and improvement of visual diagnostics.…”
Section: Resultsmentioning
confidence: 99%
“…Taking the aforementioned limitation of the genetic analysis into account, as well as the proportion of different missing genotypes, in this study, missing data were considered as being missing not at random. The EXTRA (or EST) method, which quantifies the effect of missing covariate data through full maximum likelihood modeling and adds a parameter for each covariate containing missing data, was therefore chosen due to its precise and unbiased parameter estimates when dealing with missing not at random data, as well as its ease of implementation in stepwise covariate procedures . Genotype information regarding rs115629050, located in CES1A1 exon 7, was found to be missing in 42% of the study population, which was high compared with the amount of missing data observed in the other final model‐included CES1 variants.…”
Section: Discussionmentioning
confidence: 99%
“…In case of missing categorical covariates a separate parameter for the missing group was estimated, 34 as follows (Eq. 5):…”
Section: Covariate Modelmentioning
confidence: 99%
“…44 Proportionality and correction factors were applied on RUV to test for differences between the assays and laboratories used.…”
Section: Chapas-1mentioning
confidence: 99%